Equitable partitions of Latin‐square graphs. Issue 3 (3rd December 2018) - Bailey, R. A.; Cameron, Peter J.; Gavrilyuk, Alexander L.; Goryainov, Sergey V.
Abstract: We study equitable partitions of Latin‐square graphs and give a complete classification of those whose quotient matrix does not have an eigenvalue −3.